THE CAPES INSERTION IN BASIC EDUCATION TEACHERS FORMATION IN BRASIL - Cruz e Silva Neto, Nathanael da [UNESP]; Lopes, Silvana Fernandes [UNESP]; Torres, Julio Cesar [UNESP]; Brandao, Carlos da Fonseca [UNESP] (Centro Univ Nove Julho, 2016)
This paper examines the insertion of the Coordination of Higher Education Personnel ( Capes) in basic education. Traditionally, the institution has always focused on the formation of higher education teachers, by concentrating in post-graduation. This is a bibliographic and documentary research, with reference to Capes' main teacher formation programs, namely: the Parfor, the Pibid, the Prodocencia, the Obeduc, the New Talent Program and the Life. It concludes that the actions of Capes, although they represent efforts to contribute to the improvement of basic education in Brazil, reveal themselves punctual and unable to solve the structural educational problems, historically constituted.
Keywords: Capes; Teachers formation; Basic education